STRONG FORMS OF CONTRA (1,2)*-g * -CONTINUITY - G.Ramkumar, M. Jegadeesan (Mathematical Statistician and Engineering Applications, 2022)
This paper devotes to introduce and investigate a new class of maps called contra-(1,2)*-g*-continuous maps which are weaker than contra-(1,2)*- continuity and stronger than contra-(1,2)*-g-continuity, contra-(1,2)*-?gcontinuity, contra-(1,2)*-gs-continuity, contra-(1,2)*-gsp-continuity, contra-(1,2)*-gp-continuity, contra-(1,2)*-rg-continuity, contra-(1,2)*- ?**g-continuity and contra-(1,2)*-gpr-continuity. The main results of the paper are that several properties concerning contra-(1,2)*-g*-continuous maps. Furthermore, the relationships between the contra-(1,2)*-g*- continuity and some bitopological maps as well as separation axioms are also investigated